FACTORS INFLUENCING ZAKAT PAYERS’ PREFERENCE IN DISCHARGING ZAKAT OBLIGATIONS: AN EXPLORATIVE STUDY - VIMA TISTA PUTRIANA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This research aims to explore factors influencing zakat payers’ preference in discharging their zakat obligations (i.e. paying zakat through authorized zakat institutions or giving it directly to recipients). This research was inspired by one of findings of our research on the effectiveness of zakat community development (ZCD) in Tanah Datar District. More clearly, ineffectiveness of the ZCD program undertaken was due to among others insufficient funding. This result indicates that local BAZNAS as the authorized zakat institution operated locally has not been able yet to optimize collection of zakat funds from zakat payers. This research is explorative in nature and therefore adopts a qualitative research approach. Data was collected at the end of October 2018, using Focus Group Discussion (FGD) with participants were two groups of postgraduate students majoring in Sharia Accounting and Sharia Banking at the State Islamic Institute Batusangkar. This research concludes that zakat payers’ preference in discharging their zakat obligations is influenced by factors such as zakat awareness, tradition, trust and level of income. This is the first research undertaken to explore the behavior of zakat payers in Indonesia. The result theoretical framework proposed in this study can be empirically tested in a larger population by the future research.